Pharmaceutical Practice - Rees, Judith A.; Smith, Ian.; Watson, Jennie (Edinburgh : Elsevier, 2014)
Covers a range of subjects relevant to pharmacy practice, including communication skills, managing a business, quality assurance, dispensing, calculations, packaging, storage and labeling of medicines, sterilization, prescriptions, hospital-based services, techniques and treatments, adverse drug reactions, cost-benefit, and medicines management.
Keywords: Pharmaceutical -- Practice; Pharmacy -- Practice; Drug Compounding; Pharmacy